Two new species of oribatid mites (Acari: Oribatida) from Vietnam - Manh, vu Quang; Ermilov, Sergey G.; Trinh, Dao Duy (Academia Journal of Biology, 2012)
Two new species of oribatid mites (Acari: Oribatida) Aokiella xuansoni sp. nov. Vu, Ermilov et Dao (Carabodidae) and Papillacarus benenensis sp. nov. Vu, Ermilov et Dao (Lohmanniidae Berlese, 1916), are described. Both are based on adult specimens and collected in the soil ecosystem, from the Xuan Son National park, province of Phu Tho and from the Ben En national park, Thanh Hoa province, Vietnam. Aokiella xuansoni sp. nov. is recognized by the small size of body, the surface of body with large and small foveolae; the straight, thickish, interiorly directed two pairs of setae (c1 longer than c2); the rather short setae da and la, which obviously not reaching bases of setae dm and lm, respectively. Papillacarus benenensis sp. nov. is recognized by the large size of body; the surface of body with reticulate sculpturing; rostrum undulate; prodorsal setae long, slightly thickened proximally, conspicuously ciliate on both sides; sensilli with 15 long, pectinate branches; one pair of medially incomplete transversal bands; notogaster with 18 pairs of long, conspicuously ciliate setae; posterior half of notogaster strongly neotrichous (more than 50 pairs of small, branched setae); genital setae heterogeneous; epimeres neotrichous (setal formula: 10-9-5-4).